Microbiota e colorectal cancer: a preliminary study in Portuguese patients - Silva, Ana Cristina Marques da (2019)
The colorectal cancer (CRC) is the third deadly cancer in the world, and in the last years its incidence rate has been increasing in Portugal. Given the relevance of the symbiosis between the intestinal microbiota and the host for body homeostasis, many studies have been focusing on the analysis of the microbiota associated with health and disease scenarios, namely with CRC. It is increasingly more important to know the microbial community associated with CRC, once it can be exploited as a tool for different clinical applications against CRC. As such, the present study intended to perform a preliminary characterization of the non-cultivable and cultivable bacterial community isolated from tumoral (TT) and adjacent healthy (TN) mucosa tissues of patients with CRC. Additionally, it was tested the antimicrobial potential and antibiotic resistance of cultivable bacterial isolates in order to verify how they behave under stressful conditions (i.e., presence of pathogens and antibiotics). It is also presented a short review on the applications of microorganisms or their abilities to fight CRC. In a general view it was observed some difference between the diversity of bacterial community from TN and TT samples, according to the DGGE profiles. Identical genera of bacteria were identified in TN and TT samples (e.g., Escherichia, Klebsiella, Pseudomonas), although some were only found in TN (e.g., Citrobacter) or TT (e.g., Enterococcus). Some bacterial isolates showed antimicrobial activity against Gram-positive and Gramnegative pathogens, and all of them were resistant to at least three different antibiotics. These responses help to understand the behavior of gut bacteria under infectious aggressions, which often occur in CRCaffected patients. On the other hand, given the relevance of gut microbiota on CRC development, the biotechnological abilities of bacteria have been explored as complementary or adjuvant therapeutics for controlling CRC. They mainly involve microbiota modulation through the consumption of pro- and prebiotics, and fecal microbiome transplantation, bacteriophage therapy, but also other groundbreaking strategies targeting CRISPR, essential and resistant bacterial genes, and quorum sensing systems.